Implementation of Rules of Fundamentalism among the Shafii religious groups on Mortgage issues - El-Rakib, Mohamed Ghazi Khalaf (Journal of Islamic Sciences, 2020)
The research aims to implement the rules of fundamentalism among the Shafii religious groups on mortgage issues. The researcher used the inductive and deductive approaches through reviewing the rule of fundamentalism that was verified from approved asset books, and reviewing the rule of fundamentalism that was verified from adopted asset books, in spite that the rule provided from the imam text was proved as it was, or the researcher would have used the adopted doctrine asset books in its phrasing, presentation of the doctrine sections in which the rule of fundamentalism was implemented, then statement of manner of implementation of the rule of fundamentalism among the doctrine section. The study showed many results, of which mainly: • Shafii religious groups saying: I do not know in it a disagreement that is not a consensus, but it’s an evidence. • That the thing among the Shafii religious groups might work by guidance. • That it’s allowed among the Shafii religious groups to mortgage Muslim who is unbeliever and the unbeliever Muslim of the Holy Quran, except if the mortgage was put without conditions, then it’s not allowed among some of them. • That some of the Shafii religious groups and among them ’Al Imam Al Shafii’ don’t accept but only messengers of ’Said Ibn Al Musayyib’ as they were searched and were approved to be not sent except from recognized authorities.